2020
DOI: 10.31557/apjcp.2020.21.10.2883
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional (3D) Laparoscopy Versus Two-Dimensional (2D) Laparoscopy: A Single-Surgeon Prospective Randomized Comparative Study

Abstract: experienced surgeon is able over time to regain some vision of depth. To resolve this problem, 3D imaging for laparoscopic surgery was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…Our series did not show any statistically significant difference between the 3D approach compared to the 2D one in terms of anastomotic leakage and/or bleeding and such findings have been confirmed by the pooled results of meta-analysis and by Yoon et al[ 35 ] and Wang et al[ 36 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Our series did not show any statistically significant difference between the 3D approach compared to the 2D one in terms of anastomotic leakage and/or bleeding and such findings have been confirmed by the pooled results of meta-analysis and by Yoon et al[ 35 ] and Wang et al[ 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…A comparative trial is ongoing, but preliminary results showed that the anastomotic time was really significantly lower when the anastomosis has been performed by novice surgeon. As 3D imaging can ameliorate depth perception, spatial location, hand-eye coordination, and precision during surgery, we agree with the hypothesis that these improvements can reflect on the learning curve allowing young surgeon to quickly achieve good result while it does not give the same advantages for experienced surgeons[ 36 ]. These findings are corroborated by the literature data demonstrating how both difficult and easy tasks were completed with greater precision and shorter performance time when medical students were working under 3D vision rather than 2D vision.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations